The impact of indigenous cultural and traditional practices on nature conservation perspectives: A study of the Batek Negrito in Malaysia / Teh Kate Yng - Teh, Kate Yng (Universiti Teknologi MARA Cawangan Pahang, 2020)
This study seeks to explore the cultures and traditions of one of the earliest ethnic groups, Batek Negrito, who inhabits the rainforest in Peninsular Malaysia, which are correspondingly related to their concerns on the values of forest resources and the importance of environmental protection. Taking the case on Taman Negara Pahang in Kuala Tahan, indepth interviews were conducted face-to-face and non-participant observations were employed to supplement the qualitative data from the interviews. The findings reveal that the forest protection is the prime concern for Batek who sustain themselves by hunting and gathering forest produces. Their knowledge and awareness of sustainability which have been developed over thousands of years, the aboriginal rituals and animistic beliefs about the sacred forest were also found as contributors to supportive attitudes towards nature conservation. However, this study has found two conflicting perspectives on nature conservation among the respondents: forest protection and unsustainable harvesting of forest resources. Claiming themselves as the original inhabitants of the forest lands, the Batek argued they should be granted the rights over the resources in their territories. Hence, understanding the indigenous cultural and traditional practices can contribute to even greater understanding of their perspectives on nature conservation which could help to preserve the cultural rights of the aborigines, their 'supermarket' and the national park, at the same time.